Statistics of medical imaging - 531480 Lei, Tianhu (Boca Raton, FL. : Taylor & Francis, 2012)
"Statistical investigation into technology not only provides a better understanding of the intrinsic features of the technology (analysis), but also leads to an improved design of the technology (synthesis). Physical principles and mathematical procedures of medical imaging technologies have been extensively studied during past decades. However, less work has been done on their statistical aspect. Filling this gap, this book provides a theoretical framework for statistical investigation into medical technologies. Rather than offer detailed descriptions of statistics of basic imaging protocols of x-ray CT and MRI, the book presents a method to conduct similar statistical investigations into more complicated imaging protocols"--Provided by publisher.